Effect of Electrical Stimulation Followed by Exercises in Postnatal Diastasis Recti Abdominis via MMP2 Gene Expression - Wei, Ruixue; Yu, Fenghua; Ju, Hairong; Jiang, Qingchun (Cellular and Molecular Biology, 2022)
Since abdominal muscle training is one of the most important ways to treat rectal diastasis, it is necessary to design and provide appropriate exercises to treat this problem. One of the complementary methods to achieve higher intensity training is the use of electrical muscle stimulation along with voluntary activity, which causes maximum recall in muscle units. Therefore, in the current study, the effect of electrical stimulation followed by exercises was evaluated in postnatal diastasis recti abdominis via MMP2 gene expression. For this purpose, we studied on thirty-two women who had rectal diastasis for six months and were referred to a physiotherapy clinic by a gynecologist. They were divided into the control group (n=16) and the intervention group (n=16). The distance between the two blocks of the rectus abdominis muscle and the thickness of the abdominal muscles at rest was determined by ultrasound. In the intervention group, electrical stimulation and strengthening exercises of oblique muscles were performed for six weeks. The control group did not perform any specific exercises. After six weeks, another ultrasound was performed. The expression of the MMP2 gene was measured by the real-time PCR method. Comparison of the distance between the two blocks of rectus abdominis muscle (above the umbilicus and below the umbilicus) before and after six weeks showed that in the experimental group after intervention in both areas had a significant decrease (above the umbilicus = 0.001 and below the umbilicus P = 0.03), while this distance in the control group did not decrease significantly (p >0.05). Also, in the upper part of the umbilicus, the distance between the two rectus abdominis muscle blocks in two groups after the intervention showed a significant difference (p = 0.04). Evaluation of MMP2 gene expression showed that there was no significant difference between the two groups before the intervention (p >0.05). However, after the intervention, the expression of this gene decreased significantly in the intervention group (p = 0.007). In general, the present study results showed that electrical stimulation of abdominal muscles with strengthening exercises of internal and external oblique muscles could reduce rectal diastasis and increase the thickness of these muscles in people with rectal diastasis.